1998
DOI: 10.1093/jn/128.6.1051
|View full text |Cite
|
Sign up to set email alerts
|

Excess Dietary Protein Can Adversely Affect Bone

Abstract: The average American diet, which is high in protein and low in fruits and vegetables, generates a large amount of acid, mainly as sulfates and phosphates. The kidneys respond to this dietary acid challenge with net acid excretion, as well as ammonium and titratable acid excretion. Concurrently, the skeleton supplies buffer by active resorption of bone. Indeed, calciuria is directly related to net acid excretion. Different food proteins differ greatly in their potential acid load, and therefore in their acidoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
176
3
13

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(197 citation statements)
references
References 15 publications
5
176
3
13
Order By: Relevance
“…Although the in¯uence of dietary protein on bone health has been cited as being either adverse [33] or bene®cial [34], results from the present observational study found no evidence to suggest that protein intake was negatively associated with BMD in either males or females. However, in the young adult males, the calcium:protein ratio did have an independent signi®cant inverse e ect on BMD (lumbar spine).…”
Section: Discussioncontrasting
confidence: 95%
“…Although the in¯uence of dietary protein on bone health has been cited as being either adverse [33] or bene®cial [34], results from the present observational study found no evidence to suggest that protein intake was negatively associated with BMD in either males or females. However, in the young adult males, the calcium:protein ratio did have an independent signi®cant inverse e ect on BMD (lumbar spine).…”
Section: Discussioncontrasting
confidence: 95%
“…Thus, our results when considered in relation to the existing literature suggest that higher intakes of animal proteins may have negative effect on bone health. This finding is consistent with the hypothesis that animal protein produces a large amount of endogenous acid, which leads to increase bone resorption (Barzel and Massey, 1998) and increased bone loss. Fracture is an ultimate outcome of osteoporosis.…”
Section: Discussionsupporting
confidence: 92%
“…É sugerido que dietas hiperprotéicas (origem animal) poderiam induzir a perda óssea por indução de acidose metabólica no organismo (15) . Como as proteínas animais são ricas em aminoácidos sulfurados, íons de amônia produzidos a partir desses aminoácidos levariam à redução do pH sanguíneo, ativando a reabsorção óssea que, em decorrência, levaria à perda de carbonato e citrato de Ca ósseo, mobilizados para neutralizar esse excesso de ácidos (15)(16) . O mecanismo renal representa o principal elemento compensatório para a acidose e, no idoso, essa proteção renal pode ser incompleta, podendo o osso ser usado para neutralizar essa carga ácida (13) .…”
Section: Papel Dos Macronutrientes Na Saúde óSseaunclassified
“…O excesso de proteína animal ou vegetal pode ser prejudicial à saúde óssea, mas esses efeitos podem ser modificados por outros nutrientes presentes na dieta, como o Ca, K e P (16) .…”
Section: Papel Dos Macronutrientes Na Saúde óSseaunclassified